An equilibrium model of 'global imbalances' revisited - Finn Marten Körner (Universität Hohenheim, 2011)
Global imbalances are almost universally regarded as a disequilibrium phenomenon. Caballero, Farhi, and Gourinchas (2008) challenge this notion with their dynamic general equilibrium model of global imbalances. The authors conclude that current account deficit nations need not worry about long-lasting deficits as long as the model is in equilibrium. The joint model in this paper combines the two model extensions for exchange rates and FDI which are disjunct in the original model. An analytical solution to the new joint model is neither as straightforward as for the separate models nor can previous results from calibrated simulation be confirmed without restriction. The model is highly dependent on parameter assumptions: A variation of calibrated parameters highlights the prime impact of investment costs previously assumed away. Sustainable equilibrium paths for global imbalances are much narrower in updated simulations than previously predicted. Policy recommendations on the sustainability of international debt holdings therefore need to be a lot more cautious.
Keywords: F31; F34; G15; O41; 330; international debt; financial market development; foreign direct investment; real exchange rate; international macro-finance